Алгоритмы построения модели зашумленного процесса путем коррекции закона его распределения - Алиев, Т.А.; Мусаева, Н.Ф.; Газызаде, Б.И. (Проблемы управления и информатики, 2017)
Розроблено алгоритми побудови вірогідностей моделі зашумленого процесу, яка складається з вірогідних моделей корисної складової і завади. Складено множину таких характеристик завади і корисної складової: математичне очікування, дисперсія, середні квадратичні відхилення, функції щільності розподілу та їх максимуми, а також точки перетину по осі абсцис і ординат. Показано, що використання цих множин в автоматичній системі керування дозволить визначити момент проведення профілактичної роботи і попередити зупинку проведення капітального ремонту. The authors construct algorithms for building a probabilistic model of the noisy process consisting of probabilistic models of useful component and noise. A set of such characteristics of noise and useful component as mathematical expectations, variance, mean-square deviations, distribution density functions and their maxima, as well as inflection points along the x-axis and y-axis obtained at different periods of time has been formed. It has been demonstrated that the use of those sets in an automated control system allows for determining the moment when routine maintenance should be performed, thus avoiding process shutdown required to perform a comprehensive overhaul.